FATORES QUE POTENCIALIZAM O RISCO DE AVC EM PACIENTES HIPERTENSOS NO RIO GRANDE DO SUL - Machado, Lauren De Oliveira; Panke, Gabriel; Herbele, Izadora; Rahmeier, Thais; Siochetta, Thailene Martins; Berlezi, Evelise Moraes (Salão do Conhecimento, 2019)
Trabalho desenvolvido na disciplina de Epidemiologia I/2019